Variation and Predictors of Surgical Case Costs among Urologists. Issue 4 (July 2017) - Hampson, Lindsay A.; Odisho, Anobel Y.; Meng, Maxwell V.; Carroll, Peter R.
Abstract : Introduction: : Shifts in the health care delivery system have emphasized providing cost‐efficient care. The operating room comprises a significant proportion of hospital costs. Analysis of practice variation in operating room supply use can provide insight into opportunities for cost reduction and improved efficiency without compromising outcomes. Methods: : A retrospective review was conducted of urological procedures performed at the University of California San Francisco Medical Center from September 2012 through December 2015. Supply costs for individual cases were itemized and aggregated using the institution negotiated rate. Operative time was monetized. Supply cost was analyzed with multivariate mixed effects models evaluating surgeon experience and surgeon volume. Results: : The majority of common urological procedures demonstrate significant variation among surgeons in supply, time and overall cost. Surgeon annual procedure specific volume was a significant predictor of lower cost in multivariate analysis of supply cost (p = 0.016) and correlated with a lower likelihood of the case supply cost being in the top quintile (p <0.001). Surgeon experience was not a significant predictor of absolute supply cost or being in the top quintile of supply cost. Conclusions: : Significant variation exists among supply costs of high volume procedures. Higher surgeon procedure specific volume predicts lower operating room supply costs. Targeting procedures with variation for cost optimization via standardization could have a substantial impact on operating room costs and efficiency. The experience of high volume surgeons may be useful to guide optimal supply use given their comparatively lower costs.